Downregulation of is associated with poor prognosis in patients with non-small cell lung cancer - Bojin Zhu; Yongjin Yan; Boyun Shao; Luwen Tian; Weihua Zhou (Journal of International Medical Research, 2018)
Objective To explore the prognostic significance of nicotinamide adenine dinucleotide (NAD)-dependent protein deacetylase sirtuin-6 (SIRT6), encoded by the sirtuin 6 ( SIRT6 ) gene, in a population of Chinese Han patients with non-small cell lung cancer (NSCLC). Methods Cancer tissues and normal lung tissues (>5 cm adjacent to cancer tissue) were collected from Chinese Han patients with NSCLC. Expression levels of SIRT6 and histone H3-acetyl K56 ( H3K56 ), in cancer and normal lung tissues from patients with NSCLC, were detected by reverse-transcription polymerase chain reaction, Western blot and immunohistochemistry. Correlations between SIRT6 expression and various clinicopathologic features were investigated. Results Out of 86 patients included in the study, mRNA and protein SIRT6 levels were down-regulated in NSCLC tissue versus normal lung tissue, and SIRT6 levels were inversely correlated with H3K56 levels. Positive rates of SIRT6 were significantly correlated with degree of cell differentiation, TNM stage, lymph node metastasis, overall survival and metastasis-free survival. Conclusion Downregulation of SIRT6 expression may promote NSCLC malignancy in the Chinese Han population. SIRT6 may be a potential therapeutic target in Chinese Han patients with NSCLC.